Data Protection Conflicts and Procedural Fairness in Cross-Border Digital Dispute Resolution - AllahRakha, Naeem; Axmedshaeva Mavluda; Abdurasulova Kumrinisa; Musayev Elbek; Utegenov Nurbolat (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2026)
The rapid digitalization of society has given rise to digital dispute resolution (DDR) mechanisms that are transforming traditional justice systems through online, automated, and platform-based processes. However, the rapid expansion of these mechanisms has outpaced regulatory development, leaving unresolved questions about jurisdiction, enforceability, and user protection. This study examines how conflicts between incompatible data protection regimes and the absence of uniform procedural fairness standards in cross-border digital dispute resolution (DDR) interact to create compounded rights deficits for users. Using a qualitative document analysis design combined with doctrinal legal research, the study analyses the structural incompatibility between GDPR Articles 3, 5, and 46–48 and US-based cross-border DDR platforms, and assesses the procedural fairness deficits including opacity of automated decisions, absence of human review, and foreclosure of meaningful appeal that result from platform-based dispute resolution operating outside binding procedural standards. The central finding is that these two regulatory failures are structurally interdependent: the same conditions that enable data protection violations simultaneously deprive users of the informational preconditions of a fair hearing. The study proposes an integrated regulatory framework comprising unified recognition rules conditioned on dual compliance with data protection and procedural fairness standards, a mandatory accreditation scheme for cross-border DDR providers, and regulatory sandboxes for supervised innovation. The findings provide an analytically grounded framework for addressing a compound regulatory failure that currently affects millions of cross-border DDR users.